INFLUENCE OF REPRODUCTIVE HEALTH EDUCATION VIA ANIMATION VIDEOS ON ADOLESCENT GIRLS KNOWLEDGE AND ATTITUDES - Maliki, Sitti Nurain Vidyanti; Sukesi, Sukesi; Handajani, Adianti; Purwanto, Triana Septianti (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Adolescents, especially adolescent girls, are vulnerable to reproductive health problems. This study aims to evaluate the influence of reproductive health education through animated videos on their knowledge and attitudes. Using a quasi-experimental method with a pretest-posttest design and a control group, 32 respondents aged 13-15 years who had menstruated were involved. The independent variable is the animated video, while the dependent variable is knowledge and attitude. Data was obtained through a questionnaire and analyzed using the Wilcoxon and Mann Whitney statistical tests. The results showed a significant increase in knowledge, from sufficient to good (100%), and a change in negative attitudes to positive attitudes (56.2%). Statistical analysis revealed a p-value of 0.000, indicating that animated videos are effective in improving adolescents' knowledge and attitudes. This study concludes that animated videos are an effective tool for health workers in conveying information to adolescents.